PENDAMPINGAN ANGGOTA FATAYAT NU RANTING DESA TENGARAN MEMAHAMI SEJARAH PERADABAN ISLAM BERBASIS DIGITAL BOOK - Priarni, Rina; Isnaini, Isnaini (Tahta Media Grup, 2023)
As a generation of Muslims, we need to know the historical development of Islamic Civilization. This aims to increase and increase the stability of our faith. Islamic history and civilization is an important part that cannot be separated from the lives of Muslims from time to time.Apart from that, the history of Islamic civilization is the identity of the Muslim community. So far, studying the history of Islamic civilization has only been obtained from formal educational institutions for a limited time,so that the children who continue Islam do not fully understand the contents of the history of Islamic civilization and do not really understand the benefits of studying the history of Islamic civilization. This has resulted in the history of Islamic civilization being less loved among Islamic children.The aim of this community service activity is 1) to help provide knowledge to members of the Fatayat NU Tengaran Village branch regarding the use of digital books to understand the history of Islamic civilization. (2) help provide understanding to members of the Fatayat NU branch of Tengaran Village regarding the importance of introducing the history of Islamic civilization to the children who will inherit Islam.In this mentoring activity, the methods used are lectures, questions and answers, demonstrations and practice.From this activity, members of the Fatayat NU Tengaran Village branch after taking part in the mentoring have sufficiently understood the importance of understanding the history of Islamic civilization. This is proven by the participants' enthusiasm for using digital books on the history of Islamic civilization on their cellphones/Androids and also the enthusiasm of their children to study the history of Islamic civilization through digital books. The same assistance needs to be provided in other places so that public awareness regarding understanding the history of Islamic civilization increases